Pentingnya Pemeliharaan dan Hubungan Kerja Industrial - Husnul Hotimah; Rasya Madaniah Nurul Islami; Chotir Mochammad Sholeh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Maintenance and industrial relations are two crucial aspects in human resource management that are interrelated and play an important role in maintaining the continuity and success of the organization. Effective maintenance not only maintains the quality of employee performance but also contributes to the creation of harmonious industrial relations. Good industrial relations, in turn, create a conducive work environment, increase productivity, and reduce the potential for conflict in the workplace. The purpose of this study is to dig deeper into the understanding of maintenance and industrial relations. This study uses qualitative and quantitative methods. Data collection techniques are carried out through a review of several journals that have been searched, which are related to the importance of maintenance and industrial relations. From the data that has been successfully collected, maintenance of industrial relations in the entire process of human resource management focuses on the belief that good and harmonious relations between employers and workers in the organization are very important to be fostered and maintained for the benefit of all parties involved. Failure to maintain harmonious relations can cause losses for many parties, especially employers and workers involved. Effective maintenance and good industrial relations play an important role in the success and survival of the company. Therefore, maintenance is a vital element in today's business world and needs to be managed properly.